Sonosensitive theranostic liposomes for preclinical in vivo MRI-guided visualization of doxorubicin release stimulated by pulsed low intensity non-focused ultrasound. - Rizzitelli, S. (2015)
The main goal of this study was to assess the theranostic performance of a nanomedicine able to generate MRI contrast as a response to the release from liposomes of the antitumor drug Doxorubicin triggered by the local ex- posure to pulsed low intensity non focused ultrasounds (pLINFU). In vitro experiments showed that Gadoteridol was an excellent imaging agent for probing the release of Doxorubicin following pLINFU stimulation. On this basis, the theranostic system was investigated in vivo on a syngeneic murine model of TS/A breast cancer. MRI offered an excellent guidance for monitoring the pLINFU-stimulated release of the drug. Moreover, it provided: i) an in vivo proof of the effective release of the liposomal content, and ii) a confirmation of the therapeutic ben- efits of the overall protocol. Ex vivo fluorescence microscopy indicated that the good therapeutic outcome was originated from a better diffusion of the drug in the tumor following the pLINFU stimulus. Very interestingly, the broad diffusion of the drug in the tumor stroma appeared to be mediated by the presence of the liposomes themselves. The results of this study highlighted either the great potential of US-based stimuli to safely trigger the release of a drug from its nanocarrier or the associated significant therapeutic improvement. Finally, MRI demonstrated to be a valuable technique to support chemotherapy and monitoring the outcome. Furthermore, in this specific case, the theranostic agent developed has a high clinical translatability because the MRI agent uti- lized is already approved for human use.